2020
DOI: 10.1261/rna.073783.119
|View full text |Cite
|
Sign up to set email alerts
|

siRNA potency enhancement via chemical modifications of nucleotide bases at the 5′-end of the siRNA guide strand

Abstract: Small interfering RNAs (siRNAs) can be utilized not only as functional biological research tools but also as therapeutic agents. For the clinical use of siRNA as drugs, various chemical modifications have been used to improve the activity of siRNA drugs, and further chemical modifications are expected to improve the utility of siRNA therapeutics. As the 5′ nucleobase of the guide strand affects the interaction between an siRNA and AGO2 and target cleavage activity, structural optimization of this specific posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Besides molecular modeling, experimental structure determination is an important tool in the design of new siRNA modifications and is required to visualize the conformational properties of new analogs and their interactions with MID and other Ago2 domains (Egli & Manoharan, 2019). For example, the crystal structure of 6‐mCEPh‐purine bound to MID exhibits a North C3′‐ endo pucker (Shinohara et al., 2021) and therefore does not mimic the sugar conformation of the parent AS1 ribonucleotides (Figs. 4 and 5).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Besides molecular modeling, experimental structure determination is an important tool in the design of new siRNA modifications and is required to visualize the conformational properties of new analogs and their interactions with MID and other Ago2 domains (Egli & Manoharan, 2019). For example, the crystal structure of 6‐mCEPh‐purine bound to MID exhibits a North C3′‐ endo pucker (Shinohara et al., 2021) and therefore does not mimic the sugar conformation of the parent AS1 ribonucleotides (Figs. 4 and 5).…”
Section: Commentarymentioning
confidence: 99%
“…In the recently published crystal structures of MID in complex with either 8‐Br‐AMP or 6‐mCEPh‐purine (Shinohara et al., 2021), the conformations of the ribose do not match those in the complexes with UMP and AMP or the puckers of AS1 in the structures of miRNA or siRNAs with full‐length Ago2, i.e., C2′‐ endo or C1′‐ exo (Elkayam et al., 2012; Elkayam et al., 2017; Frank et al., 2010; Schirle & MacRae, 2012). The pucker of the ribose in 8‐Br‐AMP is C4′‐ exo , possibly due to the bromine at the C8 position.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary positions that can be modified for improving potential of siRNAs to regulate gene expression is 5′ nucleobase that is responsible for the interaction between siRNA and Ago2. For instance, another study has used an adenine-derived analog, known as 6-mCEPh-pourine to modify 5′ end of siRNA that significantly improved potential of siRNA in reducing gene expression in vitro and in vivo [ 226 ]. Another experiment also revealed that 5′ end modification of siRNA by 6-mCEPh-pourine can be advantageous in promoting the generation of mature RICS by enhancing RISC stability and fixing loading orientation of siRNA duplexes [ 227 ].…”
Section: Chemical Modification Of Sirnasmentioning
confidence: 99%